Jake Drake, teacher's pet - Clements, Andrew, 1949-; Pedersen, Janet (New York : Aladdin Paperbacks, 2007)
Jake remembers the terrible days in third grade when everybody thought he was the teachers' pet.
Ages 7-10.
Keywords: Teacher-student relationships -- Fiction; Schools -- Fiction